STRESS INTENSITY FACTOR IN MATRIX-AGGREGATE CONTACT ZONE - S. N. Leonovich (Наука и техника, 2010)
The presented approach and illustrative problems clearly demonstrate significant possibilities of destruction mechanics in development of the finished theory on frost concrete and reinforced concrete destruction which is based on peculiar features of structure and texture.Calculative mechanics of destruction makes it possible to evaluate kinetics of frost destruction in terms of power and energy parameters at any combination of concrete structure and cryogenic action.